2021
DOI: 10.1038/s41598-021-88917-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of QTLs associated with spikelet-related traits and grain size in sorghum

Abstract: Although spikelet-related traits such as size of anther, spikelet, style, and stigma are associated with sexual reproduction in grasses, no QTLs have been reported in sorghum. Additionally, there are only a few reports on sorghum QTLs related to grain size, such as grain length, width, and thickness. In this study, we performed QTL analyses of nine spikelet-related traits (length of sessile spikelet, pedicellate spikelet, pedicel, anther, style, and stigma; width of sessile spikelet and stigma; and stigma pigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…We previously demonstrated that the combination of BTx623 and NOG is useful for dissecting various traits, such as those related to the photosynthetic capacity during grain filling (Ohnishi et al 2019), biomass (Kajiya-Kanegae et al 2020), spikelet morphology (Takanashi et al 2021), organophosphate pesticide sensitivity (Jing et al 2021), and seed ionome (Wahinya et al 2022). Using this population, we cloned DAI , which is present only in BTx623 because of gene duplication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously demonstrated that the combination of BTx623 and NOG is useful for dissecting various traits, such as those related to the photosynthetic capacity during grain filling (Ohnishi et al 2019), biomass (Kajiya-Kanegae et al 2020), spikelet morphology (Takanashi et al 2021), organophosphate pesticide sensitivity (Jing et al 2021), and seed ionome (Wahinya et al 2022). Using this population, we cloned DAI , which is present only in BTx623 because of gene duplication.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we identified two dominant QTLs that control plant height using the same RILs, which corresponded to Dw1 and Dw3 . These two loci were shown to pleiotropically influence the size of spikelet-related organs, such as SSs, pedicels, anthers, and styles in the same RIL population (Takanashi et al 2021). Considering that NOG has functional alleles for both genes (Kajiya-Kanegae et al 2020), qAL7 and qAL9 detected in this study likely correspond to Dw3 and Dw1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic changes in other grain yield-related traits have also accumulated to feed the world. A case in point is that grain number per panicle of both sorghum and maize cultivars increased more than their wild progenitors [ 34 , 35 , 36 ]. Bommert et al reported that grain number per panicle was negatively correlated with grain size and some other inflorescence architectures [ 37 ].…”
Section: Increased Grain Yield Through Crop Domesticationmentioning
confidence: 99%
“…To date, over 168 primarily mapped QTLs associated with grain size have been reported in sorghum. Among them, 155 QTLs located on ten chromosomes have been mapped for thousand grain weight (TGW) in various independent studies published between 1995 and 2021 [ 13 , 34 , 43 , 45 , 46 , 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] ( Figure 1 a and Table S1 ). Few QTLs related to grain size (21 QTLs for grain length, 23 QTLs for grain width, and 26 QTLs for grain number per panicle) have been identified.…”
Section: Genetic Dissection Of Grain Yield-related Traits In Sorghum ...mentioning
confidence: 99%